THE EFFECT OF ONION (Allium ascalonicum L.) COMPRES TOWARD BODY TEMPERATURE OF CHILDREN WITH HIPERTERMIA IN BOUGENVILLE ROOM DR. HARYOTO LUMAJANG HOSPITAL - Pragita Reza Riyady; Liarucha Ria Aridya; Juliningrum Peni Perdani; Hardiani Ratna Sari; Prasetyorini Dhara Ayu; Zulka Ayesie Natasa; Flowerenty Dini Dian; Sari Dewa Ayu Eka Chandra Merta; Sari Dewa Ayu Dwi Chandra Yadnya; Hikmah Devintania Kurniasti Nurul; Pratiwi Haidar Dwi; Irawan Rosita Debby; Puspitasari Melinda; Suhariyati Suhariyati (UPT Penerbitan Universitas Jember)
Hyperthermia is a condition where the bodytemperature is higher than usual , and is a symptomof a disease[1]. If not promptly treated hyperthermiamay cause an increase in respiratory rate and pulse,increased heart rate, chills, excessive sweating,increased thirst, mild to severe dehydration, andseizures[2]. Hyperthermia can occur in 1 of 2,000cases in children aged 1 to 10 years which is ascribedto the pediatric emergency department . Increasedbody temperature at an ordinary child makesparents into becoming stressed and anxious[3].Onion is a multipurpose herb that can be used tolower the body temperature[4]. Phytochemicalcompounds contained in the onions one of which isa flavanoid [5]. Flavonoids show more than onehundred kinds of bioactivity was shown among otherantipyretic effect, analgesic and anti-inflammatory[6]. Flavonoid found in onions as much as 29%.Flavonoids in onions second highest after green tea,where onions are also often used in everydayactivities within the community so it is very easy tofind in the community[5]. Red onion , besidescontaining flavonoids, also contains organic sulfurcompounds that Allylcysteine sulfoxide (Alliin) whichserves destroy the formation of blood clots. Thismakes the smooth blood circulation so the heat fromthe body can be more easily distributed to theperipheral blood vessels.Data based on the results of preliminary studiesconducted in space Bougenville dr. LumajangHaryato hospital diseases showed 10 patientstreated in the room is DHF, Seizures Fever, vomiting,GEA, pneumonia, typhoid, GEDR, bronchitis,Talasemi, and Febris. DHF disease ranked first inwhich there are 37.3 % of the top ten most prevalentdiseases are DHF or 72 out of 193 patients. Based onthe description of the background above, the writeris interested in studying the effect of onioncompress to temperature changes in patients withhyperthermia. The general objective of this studywas to analyze the effect of onion compress therapyin patients with hyperthermia treated in Bougenvilledr . Haryato Lumajang.